2012
DOI: 10.3390/medicina48020010
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Takotsubo Syndrome Related to Tracheal Intubation/Extubation

Abstract: Takotsubo cardiomyopathy is an acute, reversible left ventricular dysfunction with characteristic contractility disorder and is usually preceded by emotional or physical stress. Two cases of Takotsubo cardiomyopathy related to tracheal manipulation are presented. Both the patients had all the typical symptoms and signs of Takotsubo cardiomyopathy, and both of them recovered completely within weeks. Tracheal manipulation is a well-known stress factor during the perioperative period, and experience from these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Other respiratory conditions reportedly associated with TTS include postpartum spontaneous mediastinal emphysema, 42 , 43 pneumothorax, 44 and pulmonary hypertension. 45 , 46 In addition, TTS has been associated with invasive procedures in patients with lung disease, such as the induction of anaesthesia, 47 lung transplantation, 48 , 49 endotracheal intubation, 50 intubation failure, 51 and extubation after mechanical ventilation. 52 However, no reliable estimate of the frequency and causality is available.…”
Section: Resultsmentioning
confidence: 99%
“…Other respiratory conditions reportedly associated with TTS include postpartum spontaneous mediastinal emphysema, 42 , 43 pneumothorax, 44 and pulmonary hypertension. 45 , 46 In addition, TTS has been associated with invasive procedures in patients with lung disease, such as the induction of anaesthesia, 47 lung transplantation, 48 , 49 endotracheal intubation, 50 intubation failure, 51 and extubation after mechanical ventilation. 52 However, no reliable estimate of the frequency and causality is available.…”
Section: Resultsmentioning
confidence: 99%
“…During the second screening, articles that were not case reports (20), that were not perioperative (25) or did not fulfill the a priori revised Mayo Clinic Criteria (23) were excluded, leaving 93 articles describing 102 patients for the analysis. 13…”
Section: Resultsmentioning
confidence: 99%
“…Various perioperative factors were proposed in some of these case reports as contributing to the development of TCM through creation of a hyper-catecholamine state, including inadequate depth of general or local anesthesia, 13 tracheal manipulation during intubation and extubation, 49 parasympathetic denervation after radiofrequency atrial fibrillation ablation especially in the region of the pulmonary veins, 14 selective sympathetic reinnervation in a transplanted heart causing an exaggerated response to catecholamines, 122 exogeneous administration of epinephrine, 33 release of inflammatory mediators due to anaphylaxis (Kounis syndrome), 33 abnormal myocardial functional architecture that predisposes patients to LV outflow obstruction in the presence of hypovolemia and/or high intrinsic or extrinsic catecholamine load, 40 extreme hemodynamic and pulmonary compromise in the perioperative period, 46 excessive CO 2 absorption during laparoscopic surgery, 50 use of ergometrine after cesarean sections, 54 cardiac arrest due to other causes, 60 direct spinal cord stimulation during placement/removal of spinal cord stimulators, 66 and autonomic dysregulation during and/or after electroconvulsive therapy. 69…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review of TCM cases reported that surgery can be psychologically and emotionally taxing[33] and that numerous nonpsychological factors in the perioperative period may contribute to the development of this condition [Table 2]. [44454647484950515253] However, given the intense stress experienced by most patients undergoing surgery, and the large number of surgeries being performed across the world, cardioprotective effects of volatile agents may have a bearing on the relatively low incidence of perioperative TCM. While there is now a body of evidence from animal and in vitro studies of human myocardial tissue suggestive of ischemic preconditioning properties of volatile anesthetics,[54] its actual role in the pathogenesis and prevention of perioperative TCM needs further exploration.…”
Section: Etiopathogenesismentioning
confidence: 99%